EXPLORING THE ROLE OF BLOCKCHAIN TECHNOLOGY IN ENHANCING FINANCIAL STATEMENT TRANSPARENCY THROUGH TRIPLE-ENTRY ACCOUNTING: A SYSTEMATIC LITERATURE REVIEW - Dewayanto, Totok; Irmadhani, Aldina Syifa Nur; Luhgiatno, Luhgiatno (STIE Pelita Nusantara Semarang, 2025)
This research examines the potential of blockchain technology and Triple-Entry Accounting (TEA) in improving financial statement transparency, replacing the double-entry system that is vulnerable to manipulation. Blockchain-based TEA enables encrypted and real-time immutable records, as well as integration with smart contracts for process automation and efficiency. Through the Systematic Literature Review method, an analysis of 30 articles shows that blockchain and DLT improve data reliability and accuracy, while smart contracts reduce errors and speed up reporting. However, the implementation of these technologies still faces various barriers such as high costs, technical limitations, institutional resistance, and regulatory uncertainty, especially in Indonesia. In addition, there is a lack of academic literature that discusses the application of TEA in depth. Therefore, further research is needed to explore the empirical application of TEA, the development of auditing standards, and updating the competencies of the accounting profession in the digital era.